Innovative Process Strategies in Powder-Based Multi-Material Additive Manufacturing - Setter, Robert; Hafenecker, Jan; Rothfelder, Richard; Kopp, Sebastian-Paul; Roth, Stephan; Schmidt, Michael; Merklein, Marion; Wudy, Katrin (Journal of Manufacturing and Materials Processing, 2023)
Multi-material additive manufacturing (AM) attempts to utilize the full benefits of complex part production with a comprehensive and complementary material spectrum. In this context, this research article presents new processing strategies in the field of polymer- and metal-based multi-material AM. The investigation highlights the current progress in powder-based multi-material AM based on three successfully utilized technological approaches: additive and formative manufacturing of hybrid metal parts with locally adapted and tailored properties, material-efficient AM of multi-material polymer parts through electrophotography, and the implementation of UV-curable thermosets within the laser-based powder bed fusion of plastics. Owing to the complex requirements for the mechanical testing of multi-material parts with an emphasis on the transition area, this research targets an experimental shear testing set-up as a universal method for both metal- and polymer-based processes. The method was selected based on the common need of all technologies for the sufficient characterization of the bonding behavior between the individual materials.<br
Keywords: additive manufacturing; multi-material additive manufacturing; polymers; metals; shear testing; mechanical testing; powder bed fusion; binder jetting; electrophotography; vibration dispenser